The impacts of the atmospheric boundary layer on regional haze in North China - Qianhui Li (Nature Portfolio, 2021)
Abstract An intensive atmospheric boundary layer (ABL) experiment was conducted simultaneously at six stations arranged in a cross shape on the North China Plain (NCP) from 26 November to 26 December 2019. The impacts of the regional ABL structure on heavy haze pollution and the relationship between the ABL height and aerosol accumulation layer (AAL) depth were discussed. Bouts of downdrafts generate a persistent descending elevated inversion layer, helping the maintenance and exacerbation of haze pollution. Continuous weak wind layers contribute to the pollutants accumulation, and low-level jets promote the removal of air pollutants. The unique landform conditions of the NCP are reflected in its regional ABL structure and further affect the spatial distribution of haze pollution. Due to the drainage flow and strong downdrafts, the western stations near the mountains have a colder surface and warmer upper air masses, resulting in a more stable stratification and worse diffusion conditions; these stations also experience a thicker weak wind layer caused by increased friction. Thus, the spatial distribution of haze is heavier in the west and lighter in the east. The convective boundary layer (CBL) height declines evidently during haze episodes, usually lower than 560 m. Furthermore, as the vertical distribution of aerosols is mainly influenced by daytime thermal turbulence and maintained at night, it is appropriate to determine the CBL height using the AAL depth. However, the AAL depth is not consistent with the stable boundary layer height due to the influence of the residual layer at night.